Role of donor nerves in supercharge end-to-side nerve transfer: A rat model study of varying injury severity - Masaru Munemori; Akira Kodama; Nobuo Adachi (PLoS ONE, 2026)
Supercharge end-to-side (SETS) nerve transfer enhances motor recovery in proximal nerve injuries by providing early reinnervation. However, the optimal indications and mechanisms remain unclear. This study examined the role of donor nerves using rat models of varying injury severity to clarify the clinical indications for SETS. Eighty female Sprague–Dawley rats were assigned to five groups: Control, Mild-SETS(–), Mild-SETS(+), Severe-SETS(–), and Severe-SETS(+). The tibial nerve was transected, decellularized, and reconstructed with a 10 mm (mild) or 20 mm (severe) graft. SETS consisted of end-to-side coaptation of the donor peroneal nerve to the tibial nerve 5 mm distal to the graft. Assessments included the sciatic functional index (SFI; measured every 4 weeks), compound muscle action potentials (CMAPs), gastrocnemius weight, and immunostaining for neurofilament (NF)-positive axons and S100β-positive Schwann cells at 8 and 16 weeks. In mild models, SETS accelerated early recovery in CMAP amplitude and muscle weight without affecting long-term outcomes. In severe models, SETS showed significant increases in CMAP amplitude and muscle weight at 16 weeks. NF-positive axons and S100β-positive Schwann cells increased distal to the coaptation site at 8 and 16 weeks in mild models, whereas both distal and proximal increases were observed in severe models. Donor nerves in SETS enable early arrival of axons and Schwann cells, leading to faster motor improvement. In the long term, spontaneous recovery compensates in mild models, whereas severe models benefit from sustained donor support that promotes regeneration. SETS nerve transfer may therefore be particularly useful in selected mild cases where rapid recovery is desired, and especially in severe cases where spontaneous regeneration is insufficient.